Asymmetric Drift Map of the Milky Way Disk Populations between 8 -16 kpc with LAMOST and Gaia datasets - Xin Li; Peng Yang; Hai-Feng Wang; Qing Li; Yang-Ping Luo; Zhi-Quan Luo; Guan-Yu Wang (The Open Journal of Astrophysics)
The application of asymmetric drift (AD) tomography across different populations provides valuable insights into the kinematics, dynamics, and rotation curves of the Galactic disk. By leveraging common stars identified in both the LAMOST and Gaia surveys, alongside Gaia DR3's circular velocity curve, we conducted a qualitative exploration of asymmetric drift distributions within the Galactic disk spanning distances from 8 to 16 kpc. In the R-Z plane, we observed that the asymmetric drift is minimal near the mid-plane of the Galactic disk and gradually increases with vertical distance, resulting in a distinctive "horn" shape. Additionally, our analysis revealed that populations with higher [$\alpha$/Fe] ratios exhibit greater asymmetric drift compared to those with lower [$\alpha$/Fe] ratios. Specifically, we found the asymmetric drift around the solar location to be approximately 6 km s${\mathstrut}^{-1}$, with a median value of 16 km s${\mathstrut}^{-1}$ across the entire sample. Notably, the median asymmetric drift in the northern region of the Galactic disk (20 km s${\mathstrut}^{-1}$) surpasses that in the southern region (13 km s${\mathstrut}^{-1}$), with errors remaining within 2 km s${\mathstrut}^{-1}$. Furthermore, our investigation into mono-age stellar populations unveiled that older stellar populations tend to exhibit larger asymmetric drift and velocity dispersion, aligning closely with predictions from previous numerical models. Finally, based on chemical compositions, we observed that the median asymmetric drift of the thick disk significantly exceeds that of the thin disk and found that star formation within the thick disk primarily occurred 8-10 billion years ago, whereas the thin disk's predominant star formation period spanned 6-8 billion years ago.